Geochemistry of IODP Hole U1502B at the South China Sea rifted margin - Jiawang Wu; Zhifei Liu; Xun Yu (PANGAEA, 2022)
Here we present major and trace elements, and radiogenic Sr and Nd isotopes for 50 whole-rock samples taken from IODP Hole U1502B. During the IODP Expeditions 367/368, the drilling at IODP Hole U1502B (18°27.8798' N, 116°13.8409' E; 3763.6 m below seafloor) penetrates ~182 m into underlying basaltic basement (739.16–920.95 m) with a core recovery of 70.7%), which was generated at a rifting margin of the South China Sea (SCS). The recovered lavas show petrographic characteristics of mid-ocean ridge basalt (MORB), but suffered pervasively from hydrothermal alteration. This sequence represents the oldest SCS oceanic crust ever drilled in-situ, and offers a globally unique window to explore the hydrothermal processes during continental breakup. This dataset represents the first detailed report of hydrothermally altered basalts for the South China Sea (SCS).